Penerapan Teknologi Pemrograman Visual Lisp Untuk Meningkatkan Kompetensi Penggambaran Pada Autocad Bagi Para Guru SMK Se Kota Semarang Dan Sekitarnya - (Jurusan Teknik Mesin Politeknik Negeri Semarang), Anwar Sukito Ardjo, Rofarsyam (Teknis, 2014)
AutoCAD® widely used as computered drawing and designing tools. AutoCAD® also have ability doing a  calculation and then present the result as automation drawing technique. This will run by coding all of manual task in the form of program with Visual LISP language.  The facility of editing and compiling for Visual LISP is attached in AutoCAD®. The Visual LISP code applicable to design and make drawing work of vehicle components as mass product.  The hoisterous of assembling of car by student of  Vocational Senior High School in Indonesia  giving opportunity for himself to design the vehicle components. Visual LISP will short a design time, because calculations and drawings will automatically done. There is no materials content of Visual LISP programming in the Lesson Plan of   Vocational Senior High School in Indonesia, so it is an opportunity to introduce to some of teacher of  Vocational Senior High School  in Semarang.  The introduce of Visual LISP programming was conducted  on 1st and 15th of June 2013,  followed  by 40 teachers as participants. Result of evaluation  from participants  was  67% expressing very agree and 33% expressing to agree that technology accepted represent matter newly; 33,3% expressing very agree and 55,4% expressing to agree if contents of  Visual LISP programming continued for the others; dissimilar opportunity. Others most suggestion in order to be continued for the advanced contents of Visual LISP programming. Keywords: Visual LISP Programming, AutoCAD automation design and drawing technique.